Analysis of methanol and ethanol in virgin olive oil - Raquel B. Gómez-Coca; Rosario Cruz-Hidalgo; Gabriel D. Fernandes; María del Carmen Pérez-Camino; Wenceslao Moreda (MethodsX, 2014)
This work provides a short and easy protocol that allows the analysis of both methanol and ethanol in the static headspace of olive oil. The procedure avoids any kind of sample pre-treatment beyond that of heating the oil to allow a maximum volatile concentration in the headspace of the vials. The method's LOD is 0.55 mg kg−1 and its LOQ is 0.59 mg kg−1. Advantages of this method are: • Simultaneous determination of methanol and ethanol (the pre-existing Spanish specification UNE-EN 14110 only analyses methanol). • No need of equipment modifications (standard split injectors work perfectly). Use of a highly polar capillary GC column, leading in most cases to chromatograms in which only three dominant peaks are present – methanol, ethanol, and propanol (that is extremely positive for easy interpretation of results). • Use of an internal standard (1-propanol) to determine the concentration of the analytes, reducing the presence of error sources.